Civil liability of non-university teaching staff - Fanjul Díaz, José Manuel (Avances en Supervisión Educativa, 2011)
There is growing concern of the teacher and educational inspection by the legal responsibilities can be purchased in their professional field. In the present article deals with the issue of liability of non-university teaching from a didactic perspective and inclusive, which includes all civil cases in which a teacher may engage in the legitimate exercise of their functions. The intention is to throw a beam of light on the subject, because only through knowledge can the peace and freedom.